The Diversity Index (IDIVERSA) has a new Environmental Social and Governance (ESG) strategy: Perspectives and challenges (Research, Society and Development, 2025)
This research aims to analyze whether IDIVERSA influences the disclosure of ESG information by regulated and non-regulated companies in [B]3. Specifically, it addresses the discussion of Agency Theory as one of the main monitoring tools for regulating conflicts of interest and presents some inferences about IDIVERSA's contribution to ESG and corporate governance of companies. The research is descriptive, quantitative, and documentary, and the population is made up of companies listed on [B]3 SA, consisting of 80 companies. The results showed that, unlike other existing indexes, this index works with a grouping thesis by considering the two socially marginalized groups, and this should help to induce ESG practices in the market and attract more investments. The research offers important contributions to the discussion related to gender and racial diversity that promote significant social, environmental and governance (ESG) disclosures by providing new evidence from companies listed on [B]3, which from the perspective of Agency Theory, are concerned with reputational and image risks and meeting the demand of investors concerned with sustainability, inclusion and diversity issues.